SIFAT PERIODIK JARINGAN ANTRIAN SERI TERTUTUP DENGAN PENDEKATAN ALJABAR MAX-PLUS - Rudhito, M Andy; Wahyuni, Sri; Suparwanto, Ari; Susilo, Frans (MATEMATIKA, 2011)
Abstract. This article discussed about the properties of  closed periodic queuing network series susing max-plus algebra. The result showed that the properties of  closed periodic dinamic queuing network series can be determined by using the concept of eigen values ​​and eigen vectors of max-plus matrix in the network model. Through the max-plus eigen vector fundamental, can be determined faster early time departure of customers of departure to the next customer periodically, with a large period of max-plus eigenvalue